Adolescent idiopathic scoliosis patients treated with bracing, surgery, or observation showed no difference in behavioral and emotional function over a 2-year period. Issue 3 (20th January 2023) - Jalloh, Hulaimatu; Andras, Lindsay M.; Sanders, Austin; Iantorno, Stephanie; Hamilton, Anita; Choi, Paul D.; Skaggs, David L.
Abstract : The purpose of this study was to assess if behavior and emotional function, as measured by the Pearson Behavioral Assessment Survey for Children, Second Edition (BASC-2) in patients and parents, changes with differing treatment protocols in patients with adolescent idiopathic scoliosis (AIS). One previous study showed abnormal BASC-2 scores in a substantial number of patients diagnosed with AIS; however, no study has assessed how these scores change over the course of treatment. AIS patients aged 12 to 21 years completed the BASC-2. The 176-item questionnaire was administered to subjects at enrollment, assessing behavioral and emotional problems across 16 subscales of 5 domains: school problems, internalizing problems, inattention/hyperactivity, emotional symptoms index, and personal adjustment. Parents were given an equivalent assessment survey. Surveys were administered again after 2 years. Subject treatment groups (bracing, surgery, and observation) were established at enrollment. Patients were excluded if they did not complete the BASC-2 at both time points. Forty-six patients met the inclusion criteria, with 13 patients in the surgical, 20 in the bracing, and 13 in the observation treatment groups. At enrollment, 26% (12/46) of subjects with AIS had a clinically significant score in 1 or more subscales, and after 2 years 24% (11/46) of subjects reported a clinically significant score in at least 1 subscale ( P = .8). There were no significant differences in scores between enrollment and follow-up in any treatment group. Similar to what was reported in a previous study, only 36% (4/11) of patients had clinically significant scores reported by both patient and parent, conversely 64% (7/11) of parents were unaware of their child's clinically significant behavioral and emotional problems. Common patient-reported subscales for clinically significant and at-risk scores at enrollment included anxiety (24%; 11/46), hyperactivity (24%; 11/46), attention problems (17%; 8/46), and self-esteem (17%; 8/46). At 2-year follow-up, the most commonly reported subscales were anxiety (28%; 13/46), somatization (20%; 9/46), and self-esteem (30%; 14/46). Patients with AIS, whether observed, braced or treated surgically, showed no significant change in behavior and emotional distress over the course of their treatment, or compared with each other at 2-year follow-up.